Volunteerism culture among AL-Muthanna University Students: An Anthropological Study - Mutter Nassir, Adnan (Opción, 2019)
This examination looks at what is the important motivation to volunteer among Iraqi students via comparative qualitative research methods. The study investigates the reactions from a sample of 597 students from Muthana University across all disciplines. The finding of this study reveals that Iraqi students have strong humanistic and religious reasons to volunteer. Furthermore, career development aspect has got reasonable attention among students to volunteer. In conclusion, volunteering is an individual choice and in this manner is affected more at the individual level but at the same time is affected somewhat by full-scale level societal powers.